PENGARUH KOMBINASI PIJAT ENDORPHIN DAN MURROTAL TERHADAP NYERI PERSALINAN KALA I DI PMB NY. N PASPAN KABUPATEN BANYUWANGI: The Effect of Giving a Combination of Endorphin and Murotal Massage On Labor Pain In The Phase I - Indah Christiana; Diana Kusumawati (Jurnal Ilmiah Keperawatan (Scientific Journal of Nursing), 2021)
Introduction: During labor, uterine contractions, cervical dilatation and stretching of the lower uterine segment cause pain. Pain during labor that is not resolved properly can affect the physiological mechanisms of a number of body systems. In addition to labor pain can be overcome with endorphin massage, can also be overcome with murottal therapy. Objective : To examine the effect of endorphin and Murrotal massage therapy on labor pain in the first stage at PMB Miss. N Paspan Banyuwangi Regency. Methods: The design of this study used Quasy Experimental with pre-test – post test control group. A sample of 20 mothers who gave birth were divided into 10 women who gave birth in the treatment group and 10 women who gave birth in the control group. The measuring tools used are questionnaires and observation sheets, the data collected is then tested with the Wilcoxon Signed Rank. Results: There is an effect of a combination of endorphin and Murrotal massage on labor pain in the first stage with a significant degree of < 0.05. Conclusion: The implication of this study is to reduce labor pain in the first stage of labor by using a combination of endorphin and murrotal massage.